Sirolimus in renal transplant recipients with malignancies in Germany - Naik, Marcel G.; Arns, Wolfgang; Budde, Klemens; Diekmann, Fritz; Eitner, Frank; Gwinner, Wilfried; Heyne, Nils; Jürgensen, Jan Steffen; Morath, Christian; Riester, Udo; Heller, Katharina M; Fischereder, Michael (Clinical kidney journal, 2021)
Renal transplant recipients have an increased cancer risk. The mammalian target of rapamycin inhibitor sirolimus (SRL) has immunosuppressive and antitumour activities but knowledge about its use in recipients with cancer is limited.We retrospectively analysed 726 renal allograft recipients converted to SRL from 10 German transplant centres. Patient and graft survival were analysed depending on malignancy status prior to conversion and tumour entity.Malignancy before conversion to SRL was reported in 230 patients, with 137 patients having skin cancers and 101 having solid cancers. Cancer occurred 4.6 ± 9.4 (median 3.0) years after transplantation. Basal cell carcinoma, squamous cell carcinoma and Bowen’s disease were the most prevalent skin cancers, while carcinomas of the kidney, colon and breast were the most prevalent solid cancers before conversion. Patients with prior malignancy were older and had better renal function at conversion compared with patients without a history of cancer. After conversion to SRL, cancer incidence rates (IRs) of all tumours were lower compared with rates before conversion. Cancer IRs after conversion were higher in patients with malignancy before conversion compared with those without. Patient survival was worse in patients with solid cancers compared with patients with skin cancers or without malignancies. Biopsy-proven acute rejections in the first year after conversion were less frequent in patients with malignancy compared with those without. Graft survival and renal function in all cancer types were better than in patients converted to SRL without cancers.Conversion to SRL in patients with a history of cancer is safe regarding renal function and graft survival, while patient survival is largely dependent on tumour entity.
Advance access publication date: 14 December 2020
Gesehen am 11.11.2021